Pengaruh Kepemimpinan Transaksional dan Manajemen Pengetahuan Terhadap Kinerja Karyawan - Rahmawati (Insan Cita Bongaya Research Journal, 2022)
The purpose of this research is to examine the effect of transactional leadership and knowledge management on the performance of PT. Semen Tonasa II and III. The sample of this study were 106 managers at PT. Semen Tonasa II and III and analysis method using WarpPLS 7.0. The results showed that transactional leadership had a positive and significant effect on employee performance. That is, the better the transactional leadership, the better the performance of the employees of PT. Semen Tonasa II and III. Then, knowledge management has a positive and significant effect on employee performance. That is, the better the knowledge management, the better the performance of the employees of PT. Semen Tonasa II and III